Effects of a Growth Modulation Device on the Immature Goat Spine - Liu, Xue Cheng; Thometz, John; Schmitz, Trevor (International Journal of Orthopedics and Rehabilitation, 2017)
Background Context: A variety of spinal instrumentations has been explored to treat the early-onset scoliosis in either children or animal model. A growth modulation device (GMD) with the conception of tilting in the coronal and sagittal plane while allowing a longitudinal sliding was developed. We hypothesize our GMD will lead to higher compressive forces induced by the GMD between intervertebral regions lead to changes of vertebral endochondral ossification. Purpose: We presented a new GMD, which was evaluated by observing morphological changes of the spine within and adjacent to the instrumented segments, having a radiographic review, and performing a histological analysis. In addition, we analyzed the growth rate and pattern of the asymmetric spine. Study Design: A perspective in-vivo study of a novel growth modulation device (GMD). Methods: The four skeletally immature goats were approached via a standard thoracotomy from T6 to T10. The right side of the vertebral body was exposed and instrumented with the GMD. One goat was sacrificed at 1, 2, 3, and 6 months following spinal surgery, respectively. Radiographs and histomorphometry were performed. Results: The average Cobb angle (T2-T12) increased from 3º to 10º. The length (T6-T10) increased from 8.9cm to 12.6cm. Bony and cartilage density was greater on the instrumented side. The heights of physis were reduced (20%-33%) on the anterior aspect of the instrumented side, but less on the posterior (12%-21%). Growth spurts are greatly reduced within the instrumented segments and growth remains constant over the animal’s life, but on the vertebrae far from the instrumentation the growth increases linearly, and the growth rate is higher. Conclusions: The GMD yields a controllable impact on the bony and cartilage density, and endochondral ossification height for a growth modulation.